Challenges and opportunities of medical research in Libya - Aisha Nasef (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Medical research is needed at community, hospital and individuals levels. Governments and hospitals benefit from medical research to solve problems, identify priorities, monitoring intervention, analyzing out come and benchmarking. Medical research help in assessment of community health status.